Strategic Management and Retention of Talent: Challenges in the Portuguese Army - Rosado, David Pascoal; Romão, Ana; Lopes, Helga Santa Comba; Baltazar, Maria da Saudade; Fonseca, Dinis (Journal of Reviews on Global Economics, 2019)
Organizations are made up of people, their most important asset. The Armed Forces are no exception in this context, quite the opposite. Despite all the developments in military equipment, especially in the last century, the human component continues to be a determining factor in the overwhelming majority of the weapons systems. The investments that have been made to the military, in terms of academic, technical and operational training, have contributed to increasing their skills and abilities in a professional career that, today, is facing even more asymmetrical challenges. Different levels of motivation, different career aspirations linked to organizational constraints and different economic contexts, have led to an increasingly difficult strategic management of human resources in the military areas, such as the Portuguese Army. This article addresses the urgency of retaining talent in the Portuguese Army, at a time when this branch of the Portuguese Armed Forces is confronted with new assignments, missions and challenges.